Allergic contact dermatitis to topical steroids.* - Foti, C.; Mundo, L.; Berloco, A. (European Journal of Pediatric Dermatology, 2001)
The diagnosis of allergic contact dermatitis to topical corticosteroids is often difficult owing to the overlapping between the clinical features of allergic contact dermatitis and many dermatoses. Allergic contact dermatitis can be suspected when a dermatosis duly treated with topical corticosteroids fails to improve or even worsens. In a series of 6,285 patients tested from January 1997 to May 2001, according to the SIDAPA (former GIRDCA) standard series, supplemented with tixocortole pevalate, budesonide and hydrocortisone 17-butyrrate, 65 (1.03%) showed sensitization to one or more topical corticosteroids. These data underline the importance of introducing molecules, which are “markers” of sensitization to topical corticosteroids, in patch test standard series. Patients suffering from allergic contact dermatitis to topical corticosteroids can be treated with low-sensitizing corticosteroids such as betametasone and other compounds classified in the “C” Coopman class.